(untitled) (Al-Aasar, 2025)
Dr. Younas Javed is a distinguished name in Urdu literature who explored multiple genres, including novels, short stories, plays, and critical essays. Although he earned wide recognition through his contribution to drama writing, his novels also hold significant literary value. His notable novels-Aakhir-e-Shab, Kanjray Ka Pul, and Stount Singh Laden-demonstrate a deep sense of historical consciousness. These works vividly portray the socio-political circumstances of pre- and post-Partition India, with a special focus on the events following the 1857 revolt. Through his novels, Javed exposes the British colonial strategies that sowed discord among Hindus, Muslims, and Sikhs, ultimately facilitating imperial control over the Indian subcontinent. His narratives critically examine the manipulation and betrayal by colonial powers and their lasting impact on communal relations. Furthermore, he incorporates real historical figures such as Quaid-e-Azam Muhammad Ali Jinnah, Mahatma Gandhi, and Indira Gandhi, blending fiction with historical reality. Javed’s craftsmanship lies in his meticulous attention to detail, powerful character development, realistic dialogues, and coherent narrative structure. His fiction serves not only as a reflection of historical events but also offers a critical lens through which readers can reassess the socio-political landscape of the Indian subcontinent. The historical depth and narrative sophistication in his novels contribute significantly to the tradition of the Urdu historical novel.